38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings (University of Maribor Press, 2025)
The Bled eConference, organised by the University of Maribor, Faculty of Organizational Sciences, has been shaping electronic interactions since 1988. The theme of the 38th conference is "Empowering transformation: Shaping digital futures for all". The central theme highlights the need for a digital transformation that is focused on the well-being of individuals and society as a whole. It emphasizes the importance of inclusive and sustainable development that enables equal participation of diverse stakeholders in shaping a digital future for all—one that is grounded in ethical, social, and sustainable principles. Within this framework, digital technologies are viewed as enablers for the transformation of existing systems and solutions in a human-centered way. The goal is to foster innovation, strengthen resilience, and promote long-term societal and economic progress. The papers in this conference proceedings explore a range of topics including the opportunities and challenges of the twin transition, emerging technologies, artificial intelligence and data science, decision analytics for business and societal changes, digital innovation and business models, restructured work and the future workplace, digital health, digital ethics, digital education, smart sustainable cities, digital consumers, and the digital transformation of the public sector.